The Change in Child’s Functioning and School Readiness: Analysis of the L. S. Wygotski Approach - Smykowski, Błażej (INSTED: Interdisciplinary Studies in Education & Society, 2015)
The preschool age has a significant impact on a child school functioning. During this stage of development we can observe the changes in the meaning of natural and cultural processes which affect the ways of coping with particular tasks. Such cultural skills as using language, counting, drawing, etc. become a basis of the adaptation. Mastering those skills depends on the stage of the development of psychical functions. It is crucial to notice whether they are activated and incorporated in a cultural or rather a natural system. A child who is under the influence of the natural-activation system, though it is objectively immersed in cultural environment (such as home, backyard, kindergarten), would be more sensitive to sounds, images and smells than to their meanings. The mechanisms of such child?s adaptation are focused on physical aspects of the environment and not on social ones. Its mechanisms of adaptation are based on direct ways of behaving, but not on behaviors in which the use of the cultural skills is necessary. The earlier the change of a preschool child?s system of activation occurs, the more time it will have to develop culturally its higher psychical functions (scaffolding) to the level which increases the probability of success in school and its environment.